Green entrepreneurial orientation for enhancing SMEs financial and environmental performance: Synergetic moderation of green technology dynamism and knowledge transfer and integration - Muzaffar Asad; Tha'er Majali; Mazin Aledeinat; Dmaithan Abdelkarim Almajali; Abdel Hakim O. Akhorshaideh (Cogent Business & Management, 2023)
Currently SMEs in the developing countries like Pakistan are struggling for their survival, however, because of increasing consumer awareness, SMEs have to focus over the environmental concerns as well. For SMEs green entrepreneurial orientation is taking significant importance. Moreover, based on the catalytic effects of green technology dynamism and knowledge transfer and integration, this study evaluated their moderating roles over the relationship between green entrepreneurial orientation and two performance measures which are environmental performance and financial performance. For the said purpose, the data has been collected from 384 SMEs operating in Pakistan involved in green practices, using simple random sampling. The results drawn from structural equation modelling revealed that green entrepreneurial orientation has a significant impact over environmental as well as financial performance, moreover, the moderating role of green technology dynamism as well as knowledge transfer and integration are also significant. The overall model has been validated and the blindfolding technique confirmed the predictive validity of the model as well. The research contributed to the body of knowledge by adding to the dynamic capability theory and guided the importance of green practices to the practitioners as well as policy makers.
Keywords: 650; Entrepreneurship; Environmental performance; Financial Performance; green entrepreneurial orientation; Green Practices; Green Technology Dynamism; Knowledge Transfer and Integration; Sustainability